Differences between patients who achieved asthma control and those who remain uncontrolled after standardized severe asthma care strategy. (1st February 2022) - Matsunaga, Natasha Yumi; Gianfrancesco, Lívea; Mazzola, Taís Nitsch; Oliveira, Marina Simões; Morcillo, André Moreno; Ribeiro, Maria Ângela Gonçalves Oliveira; Ribeiro, José Dirceu; Hashimoto, Simone; Toro, Adyleia Aparecida Dalbo Contrera
Abstract: Objective: To assess clinical, functional, and inflammatory patterns of children and adolescents with severe uncontrolled asthma, and investigate the differences between patients who achieved asthma control and those who remain uncontrolled after standardized asthma care strategy. Methods: Screening all children and adolescents with asthma from the Pediatric Pulmonology Outpatient Clinic of Unicamp, Brazil, and included those with severe uncontrolled asthma according to GINA guidelines criteria. Patients were assessed at baseline and after by demographic and medication data, questionnaires (Asthma Control Test and Pediatric Asthma Quality of Life Questionnaire), Six-Minute Walk Test, skin prick test, spirometry, induced sputum, and blood collection (total immunoglobulin E and eosinophil count). Cytokine dosage was analyzed in sputum supernatant and serum by Cytometric Bead Array. Results: Thirty-three patients with severe uncontrolled asthma were included (median age 10.9 [7.00–17.60] years). All patients presented satisfactory adherence to treatment and 50% of them achieved good asthma control after six-month follow-up ( p  < 0.001). Patients who achieved asthma control reported higher intervals since their last exacerbation episode ( p  = 0.008) and higher quality of life scores ( p  < 0.001) as compared to patients who remained uncontrolled. We found no changes in lung function markers, inflammatory biomarkers, or cytokine levels between patients with uncontrolled and controlled asthma. Conclusion: Participation of six months in a structured outpatient clinic for children with severe asthma had a notable improvement in control and quality of life of patients. This demonstrates the importance of a global assessment, focused on peculiarities presented by patients with severe uncontrolled asthma.